Efectos de un programa cognitivo comportamental sobre los niveles de estrés y glucemia en pacientes con diabetes mellitus tipo II - Maigual, Luis Carlos Delgado; Hidalgo Villarreal, Guillermo Andrés; Villalobos Galvis, Fredy Hernán (Universidad y Salud, 2012)
This study determined the effects of applying a cognitive-behavioral program on stress levels and blood glucose in patients with diabetes mellitus type II in the Foundation Hospital San Pedro in San Juan de Pasto. The stress levels and blood glucose were determines for this before the implementation of the intervention program. Then the program was designed and implemented to the participants (which is supported in the process model of stress of Lazarus and Folkman), and finally its effectiveness was evaluated by comparing the measurements with respect to post-test and pre-test evaluations. The type of study was explanatory and the design was pretest - posttest type with control group. It included the participation of 16 patients who were randomly assigned to each group. The results showed statistically significant changes in reducing stress levels; while it was not thecase for blood glucose levels, although better metabolic control was observed in the experimental group. It was shown that Lazarus and Folkman model is effective in stress intervention in such patients.